Morbihan disease: A diagnostic dilemma: two cases with successful resolution - Donthi, Deepak; Nenow, Joseph; Samia, Arthur; Phillips, Charles; Papalas, John; Prenshaw, Karyn (My University, 2021)
Morbihan syndrome is a rare entity characterized by persistent erythema and solid edema of upper two-thirds of the face. Although its etiology is poorly understood, it is known to have a wide differential diagnosis and is frequently under-recognized.1–3 We report two such cases of Morbihan syndrome in patients that responded well to treatment with a combination of 2.5% hydrocortisone cream, brimonidine 0.33% topical gel, metronidazole gel and 100 mg doxycycline twice daily. This report emphasizes the necessity of biopsy for clinical correlation in cases of chronic facial edema. It also serves to highlight a potential association of Morbihan syndrome to diabetes mellitus through recently discovered pathophysiology of diabetes on the lymphatic system. It underscores the effectiveness of our therapeutic regimen in the context of other treatment regimen effectiveness. Finally, it highlights novel advances into the diagnosis and treatment of the disease.
Keywords: Dermatology; pathology; inflammatory disease; Morbihan